Symbolism in Nusantara masjid architecture: Why and wherefores - Mohd Nawawi, Norwina; Abdul Rahim, Zaiton; Abdul Majid, Noor Hanita; Denan, Zuraini; Abdullah, Fadzidah (2019)
Nusantara or the Malay Archipelago lies in South East Asia. An equatorial maritime area was rich with trades and people traffic between the islands and mainland, with its own distinct culture. The coming of Islam into the region was accepted naturally without conquest and thus pave the way into the Malay culture and manifested in the existing architecture. In the inquiry of the meaning of symbolism found in the Masjid architecture in this region, differing from traditional masjid of the middle east or India, this paper intends to demonstrate how acculturation of Islamic faith and culture of the people in the Malay Archipelago were seamlessly expressed as symbolic meanings in their masjid architecture. Through literature review and case study visits to selected existing masjid of the Nusantara, the findings denote that symbolism, within the permit of the shariah, enhances the spatial and spiritual experience of the people. In the case of a masjid in Kerinci, Jambi in West Sumatra, the symbolic meanings derived from Islamic faith and local culture, both structural and non-structural components of the masjid, were encoded, presented and communicated in the form of architectural features, gave meanings and heightened the spiritual experience of the users. Symbolic meanings in the old masjid architecture of Kerinci are simplified abstractions manifesting the worldview of the local people or society. The paper summarises that in such society, incorporating symbolism in designing a masjid to them, can enhance and exalted the spiritual level of users, and in the same process add character and soul to the masjid. This research finds historic or old vernacular masjids are the best example of how architecture can play a major role not only in providing a physical shell for the users but enhance their spatial and spiritual experiences, where, in the process able to create an identity and unique character to the place.